Internalisasi Nilai-Nilai Budaya Dalam Pelayanan Bimbingan Konseling - Andi Agustan Arifin; Rita Puspita (Peneliti.net, 2023)
Globalization with all its impacts has presented its own challenges to the world of education. These challenges cover all aspects of life with the heaviest being the humanitarian aspect, starting from cultural issues that experience erosion, shifts and changes in values ​​in society or individuals, which will eventually color the way of thinking and human behavior. Therefore, the world of education is required to be able to carry out its conservative mission as the guardian of cultural heritage. Guidance and counseling services are always dealing with and related to human needs and problems, so counseling services must always adapt to these changes in order to remain effective Counseling as a profession that relies more on communication in providing assistance services to overcome problems faced by a person, not only focus on conventional approaches (psychodynamic, behavioristic, and humanistic), but must consider cultural aspects. The main assumption in realizing the effectiveness of guidance and counseling services that are oriented to cultural values ​​is recognizing that there are basic tendencies that we have, as a way of understanding other people's cultures and understanding the limitations of our own culture. Counseling is basically a cultural encounter between counselors and counselees from diverse cultural backgrounds. Cultural orientation and accentuation in guidance and counseling must receive the counselor's attention. Cultural values, especially local culture, are important to apply in the counseling process so that they can give color.